Peran Strategi Komunikasi Efektif dalam Membentuk Karakter Anak Usia Dini - Anggraini, Elya Siska; Lubis, Siti Khodijah; Sembiring, Claudia Cresensia; Nababan, Lindawati Elisabeth; Sinaga, Lisda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The golden age period (0-6 years) is a critical phase in shaping a child’s character, where effective communication serves as a strategic tool for instilling core values, thought patterns, and behavior. This study aims to analyze the role of effective communication in early childhood character development through a library research approach, reviewing relevant and up-to-date literature. The findings indicate that caregivers’ communication patterns influence not only socio-emotional aspects but also children’s neurological development, particularly in the prefrontal cortex and limbic system, which regulate emotions and morality. A democratic communication style proves most effective in fostering cognitive skills, creativity, and conflict resolution, compared to authoritarian or permissive approaches. However, challenges in the digital era, such as high screen time (averaging 3.5 hours/day), may reduce essential face-to-face interactions. In Indonesia, 62% of parents still use one-way communication, which hinders critical thinking development. This article emphasizes the need to balance technology use with direct interaction and highlights the importance of training parents and educators in effective communication to cultivate a generation with strong character and adaptability.